Is CRISPR a fear Against Sports? - Korkut Ulucan (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2017)
One of the most worrying applications of molecular technology in sport is the gene doping, which is an outgrowth of gene therapy. In gene therapy, the missing or out- functioned gene or gene fragment is replaced with the functioning one,by the help of transfectionable devices such  as viruses.In gene doping,the interested region is mostly the genetic material for enhancing athletic  capacity.World Anti-doping Agency defined gene doping as the "non therapeutic use of cells,genes, genetic elements,or modulation of gene expression,having the capacity to enhance performance". To  date,different researchers have attempted to inject different types of genes to model organisms [1,2], but still these approaches are far from safeness in humans, even in medical area.A  new  gene  editing  strategy  gives  promise for genome editing.  Many  scientists  have  now  an  opportunity  to  edit  an  organism  genome by clustered, regularly interspaced,short palindromic repeat (CRISPR) technology.By this technology,with the help of RNA-guided nucleases, such as CRISPR Associated Protein 9 (Cas9), it is possible to modify endogenous genes by using a modified CRISPR-Cas9 system.This modified system will not only spur the development of novel molecular therapeutics for medication of diseases,but also perform targeted,highly  efficient alterations of genome sequence and gene expression [3].